Analisis Keamanan Sistem Kepegawaian dan Pengembangan Sumber Daya Manusia di Sektor Pemerintahan Dengan Metode OWASP - Nur Hariyanto, Mohammad Malik; Umam, Chaerul (Jurnal Algoritma, 2025)
Information system security plays an important role in supporting public services, particularly in the management of civil servant data and human resources. This research aims to evaluate the security of the personnel information system in the government sector in Pati Regency. This research approach uses OWASP ZAP. The findings show that the system still has a high potential for exploitation through various types of cyber attacks, such as XSS, clickjacking, CSRF, and data theft. This condition makes it very important to conduct regular IT security audits to maintain the reliability and integrity of government information systems.